Elemental concentration and potential ecological risk assessment of reef associated surface sediments of Appa Island, Gulf of Mannar Biosphere Reserve, Southeast coast of India. (March 2018) - Saravanan, P.; Krishnakumar, S.; Silva, Judith D.; Pradhap, D.; Vidyasakar, A.; Radhakrishnan, K.; Godson, Prince S.; Arumugam, K.; Magesh, N.S.
Abstract: Thirty three surface sediments were collected for the present study to assess the elemental concentration and its associated ecological risk in the reef associated surface sediments, Appa Island, Gulf of Mannar Biosphere Reserve, South east coast of India. The distribution of calcium carbonate in the reef sediments is controlled by coral debris and shell fragments whereas the Organic matter (OM) content are chiefly derived from mangroves and sea grasses. The circulation of trace elements and Fe, Mn are controlled by the fluvial process and re-suspended sediments. The concentration of Pb was primarily controlled by migration of pollutants through long shore sediment transport process. The main source of Pb in the study area is from coal incinerating power plants and coal handling operations from harbors. Highlights: The present attempt was carried out to assess the potential ecological risk status of the Appa Island. The distribution of OM and CaCO3 were locally controlled by the mangrove litters and coral debris. The surface sediment accumulated elements supplied through natural sources except Pb. The sources of the Pb in the sediments is from coal incinerating power plants and application of leaded fuels. The trace elements accumulation clearly suggests that the coral reef ecosystem is under low risk category.